Gold(i)-catalyzed access to neomerane skeletons. Issue 10 (23rd June 2017) - Tugny, Coralie; Khaled, Omar; Derat, Etienne; Goddard, Jean-Philippe; Mouriès-Mansuy, Virginie; Fensterbank, Louis
Abstract : The gold(i ) catalyzed cycloisomerization of an enynyl propargylic ester, featuring a 1, 2-acyloxy migration/intramolecular cyclopropanation sequence, opens a straightforward access to the 5, 7, 3-tricyclic skeleton of neomerane sesquiterpenes. The first total synthesis of 5- epi -valeneomerin B in 12 steps with an overall yield of 5.3% is reported. Abstract : The gold(i ) catalyzed cycloisomerization of an enynyl propargylic ester, featuring a 1, 2-acyloxy migration/intramolecular cyclopropanation sequence, opens a straightforward access to the 5, 7, 3-tricyclic skeleton of neomerane sesquiterpenes. The first total synthesis of 5- epi -valeneomerin B in 12 steps with an overall yield of 5.3% from the readily available hex-5-en-2-one is reported.